APLIKASI SISTEM PAKAR UNTUK MENENTUKAN KEPRIBADIAN SISWA KELAS XII DENGAN METODE FORWARD CHAINING BERBASIS WEB (STUDI KASUS : SMA SANTO YOSEPH) - Roelly Hoemdiana (Jurnal Informatika dan Bisnis, 2020)
Technology hold important role on preparing resource for human, therefore maintaining goodtechnology by quality and quantity is a must. It can be seen by how fast in this technology era. With a greatand modern development of technology, there is a technology that can adopt how human think calledartificial intelligence that combine knowledge and data seeking for answer of trouble that human needResearcher write what is the meaning of system, information, and system information which is thebasis of expert system, researcher also write information about artificial intelligence and role of expertsystem. Researcher use forward chaining for counting. Researcher also write about web, personality, jungpsychology, and MBTI with 16 personality of MBTI.Researcher gather data by doing field observation, such as direct observation and interview withteacher from Santo Yoseph high school, and literature review such reading book, journals, and website forreference.This application made for determine personality of students Santo Yoseph high school based onMBTI and easier for teacher of Santo Yoseph high school for gathering data counseling guidance.Through step by step research and program development, researcher make a conclusion thatapplication that researcher made can determine personality based on MBTI dan easier for teacher of SantoYoseph high school for gathering data counseling guidance.Key words : Expert system, Forward chaining, MBTI (Myers-Brigss Type Indicator), Web